Physical Environment and Hygiene status at food service establishments in a tertiary care medical college campus in Delhi: A Cross-sectional study - Boro, Pallavi; Soyam, Vishal C.; Anand, Tanu; Kishore, Jugal (Asian Journal of Medical Sciences, 2014)
Introduction: Food can be a potential source of infection and disease, right from the point of preparation to the point of consumption. It is more likely in the food service establishments where mass food is prepared. Objectives: To study the physical environment and hygiene status at food service establishments in a tertiary care teaching hospital in central Delhi. Materials and Methods: An observational cross sectional study was conducted from June-August, 2014 in medical college and associated hospital in Delhi using questionnaire to assess sanitation and environmental hygiene status. The checklist contained 12 categories with a maximum possible score of 139 for the vegetarian and 140 for the non-vegetarian food establishments. The classification of the establishments on the basis of score obtained is as follows: Grade 1 = 0-25%, Grade 2= 26-50%, Grade 3= 51-75%, Grade 4 = 76-100% Data analysis: The data was analyzed using SPSS version 20. Results: A total 13 food service establishments were included of which most (92.3 %) were operated on contractual basis. Majority (84.6 %) provided non-vegetarian food. None of the food handlers were given uniform to wear during their working hours. Few (15.2%) were using caps but those were not covering the entire hair. Conclusion: The conditions of the food establishments in the medical college campus are not of prescribed standard and needs improvement. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11533 Asian Journal of Medical Sciences Vol.6(4) 2015 76-79